Preparation and Application for Separation of Small Molecules of a New Poly(OVS-co-EDMA) Hybrid Monolithic Column - Wang, Fengqing; Wei, Aile; Zhao, Jing; Liu, Haiyan; Bai, Ligai; Yan, Hongyuan (Journal of New Developments in Chemistry, 2016)
A hybrid monolithic column was prepared using octavinyloctasilasesquioxane (OVS) as a monomer, benzoyl peroxide/dimethylacetamide (BPO/DMA) as initiator, ethylene glycol dimethacrylate (EDMA) as cross-linker, 1-dodecanol as porogenic agent and dimethylbenzene as cosolvent. A tidy skeleton, much bigger specific surface area (22.4 m2/g) and lower swelling property of the monolithic column with OVS added than the one without OVS added were determined with Scanning Electron Microscopy (SEM), Nitrogen adsorption/desorption measurements (BET) and swelling test with elute of different concentration of acetonitrile in water. Fourier-transform infrared spectra (FTIR) was taken to characterize the composition of groups. Moreover, a better separation performance for benzene series compounds under reversed phase liquid chromatography (RPLC) mode was obtained using the monolithic columns with OVS added than those without.
Keywords: Monolithic Column; Small Molecules; OVS; Swelling Property; Reversed Phase Liquid Chromatography